COMPARATIVE EVALUATION OF LMX CULTURE MEDIUM AND MODIFIED LMX CULTURE MEDIUM FOR DETECTING ESCHERICHIA COLI IN WATER - Chantarasiri, Aiya; Boontanom, Parima; Preechayan, Satinee; Panthong, Apirak; Chuenarom, Vitcha (Interprofessional Journal of Health Sciences, 2023)
Escherichia coli is used as a faecal indicator bacterium and biological parameter of water quality. Multiple tube fermentation has been widely used for determination of E. coli contamination in water. However, this standard technique has limitations particularly in the length of incubation time. An enzymatic assay using Lauryl sulphate MUG X-gal (LMX) culture media was developed as an alternative method for the rapid detection of E. coli contamination in water samples. This study proposed a modification of the traditional LMX culture medium, applied to the modified LMX culture medium for saving costs and improving the detection performance. Results determined that the modified LMX culture medium was feasibly preferable for practical water quality analysis.